(untitled) - Lipsey, Richard G. (New York, 1978)
This study guide to the main text, "Economics", includes learning objectives, review and self-test questions, answers to multiple-choice questions, exercises, short problems, answers to chapter exercises, cases and case questions. The main text, "Economics", is also available in separate volumes, "Macroeconomics" and "Microeconomics".
Keywords: Economics